Cross-border delivery of public services: How useful are EGTCs? - Annika Jaansoo; Nico Groenendijk (European Regional Science Association (ERSA), 2014)
The European Grouping of Territorial Cooperation (EGTC) is a European legal instrument designed to facilitate and promote cross-border, transnational and interregional cooperation. It was introduced in 2006 to enable public authorities of various Member States to team up and deliver joint services, without requiring a prior international agreement to be signed and ratified by national parliaments. At the end of 2013, 45 EGTCs had been established, and 15-20 EGTCs were under consideration (Committee of the Regions, EGTC Monitoring Report 2013). EGTCs in operation differ considerably in terms of size and activities, but some patterns can be discerned: most EGTCs are located in the Southern and Eastern part of the EU, and most deal with strategic cooperation for economic development (including spatial planning) rather than with concrete cross-border public service provision. Recently, EGTCs have been given a more prominent role in the institutional set-up of EU Cohesion Policy for 2014-2020. This all raises the question whether the instrument of EGTC is used for what it was originally intended for. This paper provides such an evaluation and looks at the possibilities and obstacles for cross-border cooperation in general, and in public service provision in particular, within and outside of the EGTC framework.
Keywords: H42; H70; H73; H87; R50; 330; cross-border cooperation; public services; EGTC